Business Process Reengineering and Changing Management: A Case Study of Yemen Culture Attaché in Malaysia - Al-haimi, Basheer; Hujainah, Fadhl (Universiti Malaysia Pahang, 2016)
This We embarked on a case study to help one organization with radical change for the purpose of gaining success and better performance. The organization we look at was Culture Attaché of Yemen embassy in Malaysia. From the interview data, we were able to identify the problems and obstacles and also come out with proper solutions to those identified problems. Two main issues were identified above the rest. First, the absence of using technology and the second is in the administrative part. Lewin’s model for change management was chosen to be the suitable model as a solution for the identified problems.